2015
DOI: 10.1007/s10616-015-9847-z
|View full text |Cite
|
Sign up to set email alerts
|

In vitro genotoxicity assessment of the synthetic plant growth regulator, 1-naphthaleneacetamide

Abstract: 1-Naphthaleneacetamide (NAAm) is a synthetic plant growth regulator in the auxin family that is widely used in agriculture to promote the growth of numerous fruits, for root cuttings and as a fruit thinning agent. The potential genotoxic effects of NAAm were investigated in vitro by the chromosome aberrations (CAs), and cytokinesis-block micronucleus assays in human peripheral blood lymphocytes (PBLs) for the first time. The human PBLs were treated with 20, 40, 80, and 160 lg/mL of NAAm for 24 and 48 h. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 46 publications
1
10
0
1
Order By: Relevance
“…Fori nstance,a tenolol is as elective b 1 -receptor antagonist primarily used for cardiovascular diseases, [1] while 1-naphthaleneacetamide serves as an auxin for rooting hormone. [2] As aconsequence,there is acontinued high demand for general strategies that provide access to substituted arylacetamides in as ustainable fashion.In recent years,catalyzed C À Hactivation has emerged as at ransformative tool for molecular syntheses. [3] While direct functionalizations of simple benzamides have thus been accomplished, [4] CÀHa ctivations of distal weakly coordinating acetamides via unfavorable six-membered metallacycles continue to be scarce,w ith pioneering contributions in palladium catalysis by Yu,M aiti, and Dong, among others.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Fori nstance,a tenolol is as elective b 1 -receptor antagonist primarily used for cardiovascular diseases, [1] while 1-naphthaleneacetamide serves as an auxin for rooting hormone. [2] As aconsequence,there is acontinued high demand for general strategies that provide access to substituted arylacetamides in as ustainable fashion.In recent years,catalyzed C À Hactivation has emerged as at ransformative tool for molecular syntheses. [3] While direct functionalizations of simple benzamides have thus been accomplished, [4] CÀHa ctivations of distal weakly coordinating acetamides via unfavorable six-membered metallacycles continue to be scarce,w ith pioneering contributions in palladium catalysis by Yu,M aiti, and Dong, among others.…”
mentioning
confidence: 99%
“…Fori nstance,a tenolol is as elective b 1 -receptor antagonist primarily used for cardiovascular diseases, [1] while 1-naphthaleneacetamide serves as an auxin for rooting hormone. [2] As aconsequence,there is acontinued high demand for general strategies that provide access to substituted arylacetamides in as ustainable fashion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction in the MI clearly indicates the mitodepressive and cytotoxic effects of 2,4-D in the present experiment. Similarly, Kocaman and Güven (2015) found that 1-naphthaleneacetamide (NAAm) caused statistically significant reduction both in the MI after 48 h treatment period and in the nuclear division index (NDI) after 24 and 48 h treatment periods as compared to the control groups.…”
Section: Resultsmentioning
confidence: 94%
“…Sedangkan ZPT sintetis merupakan alternatif dari penggunaan ZPT alami, karena daya kerja yang jauh lebih cepat dibandingkan dengan ZPT alami. Akan tetapi memiliki kelemahan tidak ramah lingkungan (Kocaman and Güven, 2016 Berdasarkan Tabel 8, terlihat bahwa bobot kering akar tertinggi terdapat pada perlakuan ekstrak bonggol pisang yang pengaruhnya berbeda nyata dengan perlakuan lainnya, kecuali dengan pemberian perlakuan Rootone-F dan air kelapa muda.…”
Section: Pendahuluanunclassified